Os botryllinae (TUNICATA: ASCIDIACEA) da costa tropical brasileira - Ferreira, Gledson Fabiano de Araújo (2007)
The subfamily Botryllinae is composed of colonial ascidians present in all oceans circunglobally. The botryllinids form thin encrusting sheets, with zooids seldom reaching 3mm in length. Botryllinids comprise two genera, Botryllus and Botrylloides, but the validity of the later is currently questionated. The present work aimed to describe the Botrylllinae from the Brazilian coast, studying their phylogenetic relationships based on morphological characters. All lots of botryllids from the Ascidiacea Collection of the Marine Sciences Institute (Institute de Ciências do Mar, Labomar, UFC) were examined. Twenty informative characters based on colony structure and zooid morphology, were selected for phylogenetic reconstruction. The genus Symplegma was used as outgroup. The survey on the collection revealed the following species from Brazilian coast: Botrylloides giganteum, Botrylloides nigrum, Botryllus humilis, Botryllus planus, Botryllus cf. primigenus, Botryllus cf. tuberatus, Botryllus schlosseri, Botryllus tabori e Botryllus sp. n. Among the nine species recorded, only Botryllus tabori and a new species of Botryllus are considered endemic. The cladistic analysis yielded three equally parsimonious trees, where only Botryllus schlosseri changed its position in the different topologies. The monophily of the genus Botrylloides was observed, with the ovaries located ventrally in relation to the testicles as supporting synapomorphy. Botryllus seems to be a paraphiletic genus, with three diverging clades.